High-strength weather-resistant reinforcing bar and method for manufacturing the same
Patent Information
- Application Number
- CN202511236955.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-09-01
- Publication Date
- 2026-10-16
- Estimated Expiration
- 2045-09-01
AI Technical Summary
[0007]本发明的目的在于提供一种高强度耐候性钢筋及其制备方法,该钢筋具有高强度、良好的强塑性匹配、优异的耐候性等优点,用以解决现有钢筋强度裕量不足、强塑性较低、不具有耐候性等问题
[0015] 1. This invention controls the elemental ratio of V and C in steel to ensure the precipitation of carbides while keeping the carbon content within the standard, thus ensuring that the microstructure of the steel reinforcement is pearlite, ferrite and a small amount of bainite.
Smart Images

Figure CN121272293B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of high-strength steel bars, and more particularly to a high-strength weather-resistant steel bar and its preparation method. Background Technology
[0002] As my country's construction industry continues to develop towards large-scale projects, large public buildings and high-rise buildings have increasingly complex structures, and there is a greater need for steel bars to be resistant to atmospheric corrosion. This places higher demands on the strength and weather resistance of steel bars.
[0003] Currently, 400 / 500MPa grade steel bars are commonly used in my country's construction steel industry, while foreign construction steel bars have reached the 700MPa level. For example, South Korea and Russia have both issued 700MPa steel bar standards. Compared with HRB335, HRB400, and HRB500, 600MPa grade steel bars can save 73.3%, 44.4%, and 19.5% of steel consumption, respectively. In the context of promoting "carbon peaking" and "carbon neutrality," the current status of ordinary strength steel bars as the main material for construction steel can no longer meet the needs of development.
[0004] Patent application CN114990429A discloses a high-strength earthquake-resistant steel bar HRB600E. The steel bar has the following alloy composition: C: 0.23-0.28%, Si: 0.45-0.80%, Mn: 1.30-1.50%, Cr: 0.15-0.30%, V: 0.10-0.15%, Nb: 0.015-0.030%, P: ≤0.035%, S: ≤0.035%, N: 0.015-0.025%, Ceq≤0.58%, yield strength ≥600MPa, tensile strength ≥730MPa, total elongation at maximum force ≥9%, strength-to-yield ratio ≥1.25, and yield-to-standard ratio ≤1.30. As can be seen from the embodiments of this patent, the yield strength is only 630MPa, which still cannot meet future requirements. At the same time, it lacks corrosion resistance and does not meet the weather resistance requirements.
[0005] Patent CN108374126A discloses a high-strength fine-grained steel bar with the following chemical composition by mass fraction: C: 0.15–0.45%, Si: 0.5–1%, Mn: 1–2%, P: 0.005–0.025%, S: 0.005–0.025%, Cr: 0–1%, V: 0–0.1%, Mo: 0–0.5%, Ti: 0.005–0.025%, Ca: 0.001–0.006%. O: 0.002-0.006%, balance being Fe and impurity elements. The transformation of intragranular ferrite or intragranular bainite is promoted by using Ti-Ca oxides with a size of 0.2-5 μm and their composite precipitates with MnS, resulting in a fine phase transformation microstructure under coarsened hot-rolled austenite grain size. Its composition is complex, and the preparation process is difficult to control. In the example, the yield strength is only 465 MPa, which is low, and it lacks corrosion resistance and does not meet weather resistance requirements.
[0006] Therefore, developing high-strength, weather-resistant steel bars is an inevitable trend in the development of the steel bar industry. Summary of the Invention
[0007] The purpose of this invention is to provide a high-strength weather-resistant steel bar and its preparation method. This steel bar has the advantages of high strength, good strength-plasticity matching, and excellent weather resistance, so as to solve the problems of insufficient strength margin, low strength-plasticity, and lack of weather resistance of existing steel bars.
[0008] The technical solution adopted by the present invention to solve the above problems is as follows: a high-strength weather-resistant steel bar, wherein the chemical composition of the steel bar by mass percentage is: C: 0.32-0.45%, Si: 0.60-1.00%, Mn: 1.40-2.00%, V: 0.25-0.30%, N: 0.02-0.03%, with the remainder being Fe and unavoidable impurity elements; the microstructure of the steel bar is a complex phase of ferrite, pearlite and bainite, wherein the content of pearlite is more than 70% by volume and the content of ferrite is 5-25% by volume.
[0009] Secondly, the present invention provides a high-strength weather-resistant steel bar for preparing the aforementioned high-strength weather-resistant steel bar, comprising the following process steps: hot metal pretreatment, converter smelting, ladle refining, continuous casting, and continuous rolling. The specific process is as follows:
[0010] (1) Hot metal pretreatment: Hot metal pretreatment reduces impurity elements in steel, ensuring that the S content is less than 0.002% after desulfurization;
[0011] (2) Converter smelting + ladle refining: High-quality scrap steel is added for converter smelting. The content of inclusions in the steel is controlled by degassing, desulfurization and argon blowing in the later stage of refining. Cored wire containing RE is fed in during the refining process.
[0012] (3) Continuously cast into square or rectangular billets;
[0013] (4) Continuous rolling into steel bars.
[0014] Compared with the prior art, the present invention can achieve at least one of the following beneficial effects:
[0015] 1. This invention controls the elemental ratio of V and C in steel to ensure the precipitation of carbides while keeping the carbon content within the standard, thus ensuring that the microstructure of the steel reinforcement is pearlite, ferrite and a small amount of bainite.
[0016] 2. This invention controls the rolling and cooling process of steel bars, and feeds cored wire containing RE during the refining process. The rolling and cooling process helps V to precipitate in ferrite, which can inhibit ferrite grain growth. This not only refines the grains, but also strengthens the steel bars through precipitation and improves their toughness.
[0017] 3. This invention achieves excellent mechanical properties and weather resistance in steel bars by controlling the types and contents of elements, especially the ratio of V and C, combined with the preparation process. The yield strength of the steel bars is 700-800 MPa, the tensile strength is 900-1100 MPa, the elongation after fracture is ≥15%, the maximum force total elongation (Agt) is ≥7%, and the corrosion rate in the 72-hour cyclic immersion corrosion test is ≤2.9 g / m. 2 ·h.
[0018] In this invention, the above-described technical solutions can be combined with each other to achieve more preferred combinations. Other features and advantages of this invention will be set forth in the following description, and some advantages may become apparent from the description or be learned by practicing the invention. The objects and other advantages of this invention can be realized and obtained from what is particularly pointed out in the description and drawings. Attached Figure Description
[0019] The accompanying drawings are for illustrative purposes only and are not intended to limit the invention. Throughout the drawings, the same reference numerals denote the same parts.
[0020] Figure 1 This is a typical microstructure diagram of high-strength weather-resistant steel bars. Detailed Implementation
[0021] This invention provides a high-strength weather-resistant steel bar and its preparation method. The steel bar has the characteristics of high strength, weather resistance and simple production process, which can solve the problems of insufficient strength margin, low strength and plasticity and lack of weather resistance of existing steel bars.
[0022] Regarding the first aspect, the present invention controls the elemental ratio of V and C in the steel to ensure the precipitation of carbides while ensuring that the carbon content does not exceed the standard, and controls the microstructure of the steel bars to be pearlite, ferrite and a small amount of bainite. Furthermore, by introducing RE elements, the present invention achieves high strength, high plasticity and excellent weather resistance of the steel bars.
[0023] The chemical composition of the high-strength weather-resistant steel bar provided by this invention, by mass percentage, is as follows: C: 0.32-0.45%, Si: 0.60-1.00%, Mn: 1.40-2.00%, V: 0.25-0.30%, N: 0.02-0.03%, RE: 0.03-0.10%, with the remainder being Fe and unavoidable impurity elements.
[0024] The reasons for limiting the composition of the billet in the high-strength weather-resistant steel bars and their preparation method in this invention will be explained. Hereinafter, only the percentage of mass in the composition will be used.
[0025] C: Carbon is an essential element for increasing strength, but it also reduces the weldability of materials. When the carbon content is below 0.32%, it will reduce the strength of the steel bars, but excessive carbon content will adversely affect the weldability and toughness of the steel bars. Considering both aspects, the C content should be controlled between 0.32% and 0.45%, preferably between 0.35% and 0.45%.
[0026] Silicon (Si): As a deoxidizing element and a solid solution strengthening element, silicon can improve the strength of steel. However, excessive silicon content can reduce the low-temperature toughness and weldability of steel. Therefore, the Si content should be controlled between 0.60% and 1.00%.
[0027] Manganese (Mn) is an essential element for ensuring the strength and toughness of steel. It not only delays the ferrite phase transformation and refines ferrite grains, but also combines with sulfur (S) to form MnS, preventing the formation of FeS at grain boundaries and thus avoiding hot cracking. To ensure high-strength steel reinforcement, the Mn content needs to be controlled above 1.30%. However, excessively high Mn content will cause central segregation, reducing toughness and weldability. Therefore, the Mn content is controlled between 1.40% and 2.00%, preferably between 1.50% and 1.90%.
[0028] Vanadium (V) is a microalloying element with significant precipitation strengthening effects. It can form V(C,N) precipitates with nitrogen, thus providing precipitation strengthening and inhibiting ferrite grain growth. To achieve these effects, the V content is controlled at 0.25–0.30%.
[0029] Nitrogen (N) can form V(C,N) with vitamin C, increasing strength. However, excessive N content will affect the toughness of the material, especially its low-temperature toughness. Therefore, the N content should be controlled between 0.02% and 0.03%.
[0030] RE: Rare earth element RE is the key element of this invention. It can be dissolved into the Fe lattice, thereby reducing the segregation of inclusions at the grain boundaries, improving the corrosion resistance and weather resistance of the steel reinforcement. To obtain the required weather resistance, the amount of RE added is 0.03-0.10%, preferably 0.04-0.08%. The RE element can contain one or more of the lanthanide elements such as Ce, La, and Y, preferably a mixed rare earth element with lower cost.
[0031] S and P: Impurity elements in steel, which significantly reduce plasticity, toughness and weldability. Their content should be as low as possible without significantly increasing costs, and should be controlled below 0.045%. Preferably, the S content is below 0.002% and the P content is below 0.02%.
[0032] In a preferred embodiment, the microstructure of the reinforcing steel is a complex phase of ferrite, pearlite, and bainite, wherein the pearlite content is 70% by volume or more, and the ferrite content is 5-25% by volume. To further improve the mechanical properties of the reinforcing steel, the present invention increases the carbon content of the reinforcing steel, adjusting the microstructure of the reinforcing steel to a complex phase structure with pearlite as the main component, ferrite as a secondary component, and a small amount of bainite. Although pearlite has lower plasticity and toughness than ferrite, its strength is significantly higher than ferrite. Therefore, a higher strength reinforcing steel can be obtained by using pearlite as the main component. Thus, the pearlite content is 70% by volume or more, preferably 75-93% by volume, more preferably 80-90% by volume. Ferrite is indispensable for the toughness and plasticity of the reinforcing steel. By controlling the ferrite content to 5-25% by volume, the plasticity and toughness of the reinforcing steel can be ensured. The ferrite content is preferably 5-23% by volume, more preferably 6-15% by volume. A small amount of bainite can ensure the strength of the reinforcing steel. The bainite content is preferably 2-10% by volume, more preferably 2-5% by volume.
[0033] In a preferred embodiment, the average grain size of the ferrite is ≤8μm. The inventors have found that by controlling the grain size of the ferrite, the yield strength and tensile strength of the reinforcing steel can be further improved while ensuring plasticity and toughness. The preferred average grain size of the ferrite is 1 to 8μm, and more preferably 2 to 7μm.
[0034] In a preferred embodiment, the reinforcing steel has a yield strength of 700–800 MPa, a tensile strength of 900–1100 MPa, an elongation after fracture ≥15%, a maximum force total elongation (Agt) ≥7%, and a corrosion rate ≤2.9 g / m in a 72-hour cyclic immersion corrosion test. 2 ·h.
[0035] In a preferred embodiment, the reinforcing steel has a yield strength of 720–790 MPa, a tensile strength of 950–1080 MPa, an elongation after fracture of 16%–25%, a maximum force total elongation (Agt) of 8%–13%, and a corrosion rate of 1.0–2.7 g / m in a 72-hour cyclic immersion corrosion test. 2 h, preferably 1.0~2.5g / m 2 •h, more preferably 1.0~2.3g / m 2 ·h.
[0036] In a preferred embodiment, the microstructure of the reinforcing steel contains RE-Mn precipitates and RE-Mn-V(C,N) composite precipitates. The inventors have discovered that the formation of RE-Mn precipitates through the interaction of RE and Mn specifically includes RE-Mn phase, RE-Mn carbide phase, RE-Mn nitride phase, and / or RE-Mn carbonitride phase. These RE-Mn precipitates can form a dense composite oxide film of Mn and RE during the corrosion process of the reinforcing steel, improving the bonding force between the film and the steel matrix, inhibiting the penetration of corrosive elements, and simultaneously providing a highly stable composite oxide film that reduces the corrosion current density on the steel surface, further improving corrosion resistance. The precipitates are preferably nanophases. Furthermore, the addition of 0.25-0.30% V to the reinforcing steel allows V to form RE-Mn-V(C,N) composite precipitates with RE and Mn during smelting. This utilizes the strong bonding force between V and C and N to provide more nucleation sites, promoting the precipitation of RE and Mn and refining the size of the precipitates.
[0037] The second method, as described in this invention, provides a high-strength weather-resistant steel bar and its preparation method, comprising the following steps: hot metal pretreatment, converter smelting, ladle refining, continuous casting, and continuous rolling. The specific process is as follows:
[0038] (1) Hot metal pretreatment: Hot metal pretreatment reduces impurity elements in steel, ensuring that the S content is less than 0.002% after desulfurization;
[0039] (2) Converter smelting + ladle refining: High-quality scrap steel is added for converter smelting. The content of inclusions in the steel is controlled by degassing, desulfurization and argon blowing in the later stage of refining. Cored wire containing RE is fed in during the refining process.
[0040] (3) Continuously cast into square or rectangular billets;
[0041] (4) Continuous rolling into steel bars.
[0042] In a preferred embodiment, RE is added in the form of cored wire during the ladle refining process. The cored wire can be a rare earth cored wire, such as one or more of Cr, La, and Y, preferably a mixed rare earth, or rare earth silicon-calcium, rare earth magnesium cored wire, etc. The inventors have also discovered that when RE-Mn cored wire is used, RE-Mn forms pre-alloyed clusters in the molten steel, increasing the nucleation density of subsequent precipitates. Furthermore, after subsequent casting and continuous rolling processes, RE-Mn precipitates are formed in the steel reinforcement matrix.
[0043] RE-Mn-V(C,N) composite precipitates significantly improve the corrosion resistance and weather resistance of steel bars, while also increasing their strength. Preferably, the RE-Mn cored wire contains RE-Mn alloy powder, which is preferably nano-powder with an average particle size of less than 100 nm.
[0044] In a preferred embodiment, the continuous casting adopts full-process protective casting, the target superheat of the molten steel in the tundish is ≤25°C, and after continuous casting, it enters the slow cooling pit for treatment.
[0045] In a preferred embodiment, the continuous rolling process involves a heating temperature between 1050 and 1100°C, a heating time between 180 and 240 minutes, an initial rolling temperature between 1000 and 1050°C, and a final rolling temperature between 850 and 900°C. The heating temperature of 1050–1100°C ensures that V is fully dissolved in austenite while preventing excessive coarsening of austenite grains, and controls temperature fluctuations within the furnace to within ±10°C. The heating time of 180–240 minutes ensures uniform temperature throughout the billet, resulting in a uniform distribution of V within the austenite. The initial rolling temperature of 1000–1050°C ensures that the billet possesses good plasticity and deformation capacity. The continuous rolling process includes roughing and finishing stages. In the roughing stage, a large reduction is used, with the reduction rate per pass controlled at 15%-25%. Through 4-6 passes, the as-cast structure is broken up, and internal defects in austenite are increased, providing more nucleation sites for subsequent V precipitation. In the finishing stage, the final rolling temperature is controlled at 850-900℃. A smaller reduction is used in the finishing stage, with a reduction rate per pass of 5%-10%, and 3-4 passes are performed. This precisely controls the size and surface quality of the steel bar, while ensuring V precipitation and strengthening the effect of inhibiting ferrite grain growth.
[0046] In a preferred embodiment, the cooling process after rolling involves initial rapid cooling to 600-650°C, followed by air cooling to room temperature, with a product yield rate of 11-16 m / s. The rapid cooling, which is 10-20°C / s to 600-650°C, can suppress the precipitation of coarse carbides and ensure the precipitation of RE-Mn precipitates at grain boundaries. When the temperature drops below 600°C, the cooling rate can be reduced, for example, by air cooling to room temperature. Through two-stage cooling, the formation of martensitic phases due to excessively rapid cooling can be avoided, thus preventing the reduction of the plasticity and toughness of the steel reinforcement.
[0047] The above-described production process facilitates the precipitation of V in ferrite, inhibits ferrite grain growth, and provides precipitation strengthening. Through this rolling method, fine ferrite grains with a size ≤8μm can be obtained.
[0048] The preferred embodiments of the present invention will now be described in detail with reference to the accompanying drawings, which constitute a part of the present invention and are used together with the embodiments of the present invention to illustrate the principles of the present invention, but are not intended to limit the scope of the present invention.
[0049] Example
[0050] Examples 1-5 and Comparative Examples 1-3 all used the following process to prepare steel bars: (1) KR desulfurization, the S content after desulfurization is less than 0.002%; (2) Converter smelting + LF refining, high-quality scrap steel is added for converter smelting, and the inclusion content in the steel is controlled by degassing, desulfurization and argon blowing in the later stage of refining; (3) Continuous casting: the target superheat of the molten steel in the ladle is ≤25℃, and it is treated in the slow cooling pit after continuous casting; (4) Continuous rolling. The elemental composition of Examples 1-5 and Comparative Example 3 meets the requirements of the present invention, while the elemental composition mass percentage of the steel bars of Comparative Example 1 and Comparative Example 2 does not meet the requirements of the present invention. The differences in their elemental composition are shown in Table 1. The S content of the steel bars of the above examples and comparative examples is less than 0.002%, the P content is less than 0.01%, and RE is mixed rare earth LaCe.
[0051] Example 1: Microstructure diagram of the reinforcing steel bar as shown below. Figure 1 As shown.
[0052] Table 1. Chemical composition (wt, %) of the steel bars in Examples 1-5 and Comparative Examples 1-3
[0053] Example 1 0.36 0.87 1.80 0.26 0.025 0.052 Example 2 0.37 1.00 1.65 0.25 0.020 0.042 Example 3 0.43 0.60 1.74 0.27 0.028 0.056 Example 4 0.36 0.91 1.40 0.30 0.030 0.048 Example 5 0.40 0.75 1.50 0.25 0.020 0.045 Comparative Example 1 0.30 0.76 1.65 0.22 0.020 0.050 Comparative Example 2 0.41 0.80 1.79 0.28 0.026 0 Comparative Example 3 0.39 0.86 1.61 0.29 0.028 0.044
[0054] The continuous rolling process parameters for Examples 1-5 and Comparative Examples 1-3 are shown in Table 2. In Examples 1-4, Comparative Examples 1 and 3, the rare earth addition method is RE-Mn master alloy cored wire, wherein the particle size of RE-Mn master alloy is 80nm, and RE is LaCe mixed rare earth. In Example 5, the rare earth addition method is rare earth silicon-calcium cored wire. Comparative Example 2 does not use cored wire containing RE. In addition, the finished product rate in the continuous rolling process of the above examples and comparative examples is 11-16m / s.
[0055] Table 2. Process parameters of the reinforcing bars in Examples 1-5 and Comparative Examples 1-3
[0056]
[0057]
[0058] The mechanical properties and ferrite grain size of Examples 1-5 and Comparative Examples 1-3 are shown in Table 3.
[0059] Table 3 Mechanical properties and grain size of the reinforcing bars in the examples and comparative examples
[0060]
[0061] The results of the periodic immersion corrosion test of Examples 1-3 and 5 and Comparative Example 2 are shown in Table 4.
[0062] Table 4. Periodic wetting corrosion test results for the examples and comparative examples.
[0063] Example 1 2.125 Example 2 2.253 Example 3 2.098 Example 5 2.706 Comparative Example 2 4.467
[0064] Comparison revealed that Comparative Example 1 had low C and V content, insufficient strengthening effect of V, and its microstructure, yield strength, and tensile strength did not meet requirements. Comparative Example 2, which did not contain rare earth elements, exhibited a 72-hour cyclic immersion corrosion rate of 4.467 g / m³. 2 ·h, similar to conventional high-strength steel bars, is not a weathering steel, while the 72-hour immersion corrosion rates of Examples 1-3 and 5 are 2.125 g / m. 2 ·h、2.253g / m 2 ·h、2.098g / m 2 ·h and 2.706g / m 2Compared to Comparative Example 2, Example 5 exhibits significantly improved corrosion resistance and excellent weather resistance. Example 1 introduces rare earth elements in the form of RE-Mn intermediate alloy cored wire, forming RE-Mn precipitates and RE-Mn-V(C,N) composite precipitates in the microstructure of the reinforcing steel. These precipitates can form a dense composite oxide film of Mn and RE during steel corrosion, improving the adhesion between the film and the steel matrix, inhibiting the penetration of corrosive elements. Simultaneously, the composite oxide film is highly stable, reducing the corrosion current density on the steel surface and exhibiting excellent weather resistance. Example 5 uses rare earth silicon-calcium cored wire, and its corrosion resistance is also significantly improved compared to Comparative Example 2. The final rolling temperature and cooling process of Comparative Example 3 do not meet the requirements, resulting in the appearance of a certain amount of martensite in the microstructure of the reinforcing steel, leading to decreased ductility.
[0065] Comparative analysis reveals that this invention, based on a unique steel element composition and preparation process, achieves excellent mechanical properties and weather resistance in reinforcing bars. The yield strength is 700–800 MPa, the tensile strength is 900–1100 MPa, the elongation after fracture is ≥15%, the maximum force total elongation (Agt) is ≥7%, and the corrosion rate in a 72-hour cyclic immersion corrosion test is ≤2.9 g / m³. 2 •h, possesses excellent mechanical properties and weather resistance.
[0066] The above description is only a preferred embodiment of the present invention, but the scope of protection of the present invention is not limited thereto. Any changes or substitutions that can be easily conceived by those skilled in the art within the scope of the technology disclosed in the present invention should be included within the scope of protection of the present invention.
Claims
1. A high-strength weather-resistant steel bar, characterized in that, The chemical composition of the steel reinforcement, by mass percentage, is as follows: C: 0.32~0.45%, Si: 0.60~1.00%, Mn: 1.40~2.00%, V: 0.25~0.30%, N: 0.02~0.03%, RE: 0.03-0.10%, with the remainder being Fe and unavoidable impurity elements. The microstructure of the steel reinforcement is a complex phase of ferrite, pearlite, and bainite, with the pearlite content being 75~93% by volume, the ferrite content being 5~23% by volume, and the bainite content being 2~10% by volume; the average grain size of the ferrite is ≤8μm.
2. The high-strength weather-resistant steel bar according to claim 1, characterized in that, The reinforcing steel has a yield strength of 700-800 MPa, a tensile strength of 900-1100 MPa, an elongation after fracture ≥15%, a maximum total elongation (Agt) ≥7%, and a corrosion rate ≤2.9 g / m in a 72-hour cyclic immersion corrosion test. 2 ·h.
3. The high-strength weather-resistant steel bar according to claim 1, characterized in that, The microstructure of the steel reinforcement contains RE-Mn precipitates and RE-Mn-V(C,N) composite precipitates.
4. A method for preparing high-strength weather-resistant steel bars, characterized in that, The method for preparing the high-strength weather-resistant steel bars according to any one of claims 1 to 3 includes the following process steps: hot metal pretreatment, converter smelting, ladle refining, continuous casting, and continuous rolling. The specific process is as follows: (1) Hot metal pretreatment: Hot metal pretreatment reduces impurity elements in steel to ensure that the S content is less than 0.002% after desulfurization; (2) Converter smelting + ladle refining: High-quality scrap steel is added for converter smelting. The content of inclusions in the steel is controlled by degassing, desulfurization and argon blowing in the later stage of refining. Cored wire containing RE is fed in during the refining process. (3) Continuously cast into square or rectangular billets; (4) Continuous rolling into steel bars.
5. The method for preparing high-strength weather-resistant steel bars according to claim 4, characterized in that, The continuous casting process adopts full-process protective casting, with the target superheat of the molten steel in the tundish ≤25℃, and after continuous casting, it enters the slow cooling pit for treatment.
6. The method for preparing high-strength weather-resistant steel bars according to claim 4, characterized in that, The heating temperature is between 1050 and 1100℃, and the heating time is between 180 and 240 minutes.
7. The method for preparing high-strength weather-resistant steel bars according to claim 4, characterized in that, The initial rolling temperature is 1000℃~1050℃, and the final rolling temperature is 850~900℃.
8. The method for preparing high-strength weather-resistant steel bars according to claim 4, characterized in that, The cooling process after rolling is to cool to 600-650℃ at a rate of 10-20℃ / s, and then air cool to room temperature, with a product yield of 11-16m / s.
Citation Information
Patent Citations
High-strength fine grain rebar and preparation method thereof
CN108374126A
640MPa-grade fine-grain high-toughness aseismic steel bar and preparation method thereof
CN116926432A
GPa-grade ultrahigh-strength anti-fatigue steel for ocean engineering and production method of GPa-grade ultrahigh-strength anti-fatigue steel
CN119433351A